2019
DOI: 10.1186/s13071-018-3285-7
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of the presence of genotype-1 of Japanese encephalitis virus in Culex gelidus in Indonesia

Abstract: BackgroundJapanese encephalitis has become a public health threat in Indonesia. Three genotypes have been recorded in Indonesia, i.e. genotype II (GII), genotype III (GIII) and genotype IV (GIV). Genotype I (GI) and genotype V (GV) have never been reported in Indonesia.ResultsA Japanese encephalitis virus (JEV) belonging to the genotype I-a (GI-a) has been isolated for the first time from a Culex gelidus mosquito in the Province of Jambi, Indonesia. This virus is related to a 1983 isolate from Thailand whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…Relevant to the case we describe, JEV transmission in Indonesia is widespread and is now endemic in 94% of the country's provinces, including the popular tourist island of Bali [15,16]. JEV infections in travelers to Bali from non-endemic countries like Australia have been previously reported [17][18][19].…”
Section: Discussionsupporting
confidence: 53%
“…Relevant to the case we describe, JEV transmission in Indonesia is widespread and is now endemic in 94% of the country's provinces, including the popular tourist island of Bali [15,16]. JEV infections in travelers to Bali from non-endemic countries like Australia have been previously reported [17][18][19].…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, the number of our collected Aedes mosquitoes may be insufficient for detection of Aedes -borne arboviruses by virus isolation. Survey of JEV in Culex mosquitoes revealed that the MIR of JEV in Indonesia was 0.06 (1/1,485) [ 16 ]. Recently in China, 10 of 511 pools of Culex mosquitoes were positive by RT-PCR for detection of JEV genome, and the MIR of JEV was estimated at 0.91 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serum was separated from the blood sample by centrifugation at 5000 rpm for 5 mins at 4°C and aliquoted in properly labeled vials. Tonsil sample of around 1gram was collected from slaughtered pig and stored in RNA later (Ambion, Thermo Fischer Scientific, USA) [16]. Both the serum and the tonsil tissues were stored at −80°C until further processing.…”
Section: Methodsmentioning
confidence: 99%
“…The Nakayama and Beijing-1 prototype strains and all other strains isolated from pigs and mosquitoes before 1994 belong to GIII [15]. However, there are reports indicating recent introduction of GI strain in pigs and mosquitoes [16, 17]. It has also been reported that GI has slowly replaced GIII strain and can become a dominant genotype because of contribution of several viral, environmental and host factors [18].…”
Section: Introductionmentioning
confidence: 99%